Victimological Study of Narcotics Abusers Using A Restorative Justice Approach at The BNN Jawa Timur - Djoko Sumariyoanto (Jurnal Hukum Lex Generalis, 2025)
This study is a normative legal study supplemented by data and interviews, where the data shows that victims of drug abuse have been subjected to legal proceedings and sentenced to prison by court decisions. This approach of imposing punishment has proven ineffective in reducing drug abuse and has instead led to an increase in the number of repeat drug offenders in society. Therefore, penal mediation by law enforcement officials using a restorative justice approach is needed to achieve recovery and healing from drug addiction. This will protect victims of drug abuse and, more importantly, be accepted back their families and into society.